Government’s Responsibilities in Handling Cases of Child Sexual Abuse in Samarinda - Suryaningsi surya; Edi Rachmat; Wingkolatin Wingkolatin; Atika Yuliana Ichsani (Salasika, 2022)
Sexual violence in the city of Samarinda has increased since 2020 when the Corona Virus spread in Indonesia. The purpose of this research is to investigate the government's responsibility to handle cases of sexual abuse crimes against children in the city of Samarinda. The research method is descriptive qualitative with a narrative approach. Indeep interviews were conducted by meeting employees who were assigned to the Women and Children Empowerment Service in Samarinda City. The results of research on the government's limitations in handling victims of sexual assault cases due to the COVID-19 pandemic. Conclusion: The government's responsibility rests with the Samarinda City Women and Children Empowerment Service. Various efforts have been made such as improving regulations, socializing, collecting data, receiving public complaints, conducting reviews, monitoring, evaluating, and supervising violations of child protection.